Projeto sócio-educacional: a reflexão sobre os fundamentos do seu sucesso a partir da ação comunicativa, o significado e sentido e a metodologia - Campos, Douglas Aparecido de (Universidade Federal de São Carlos, 2005)
Along of three-half years in collect data, in interactions, in interventions, in nderstandings and a perceptions in a social-educational project, we developed a study whose objective was to analyze the motive about its success, now that it owned to municipal government and so, was conditioned to the political changes of incuse partisan that, habitually dismantled the social-educational projects. We had a hypothesis that was: the project kept remained firm, united, efficient and in action, although few conditions, due the methodology used, that generated student s success, permanency and assiduity along seventeen years. The methodology utilized for the collect data was the qualitative research approach and used instruments, such as: the observation, field diary, interview, questionnaire, picturies, newspaper clipping and others records. The main focus for the analysis of the results was the relations, interactions and longings between people who was involved daily in that social-educational project. For this, we choose three main categories: 1 The strong teacher s presence as principal point of the project: sense and meaning; 2 The teacher s methodology used in the project, even so assystematic form and; 3 The contents as something that brings sense and meaning to the community. The results denoted that the success of that project may be associated to: 1 The students made identical process with the contents of the project; 2 The community made the management of the project and the Public Administration participated as collaborator; 3 The students was motivated in the process of the learning (followed up the teacher s methodology; 4 - The students got leisure in the activities of the project; 5 The teacher s communicative action overcomed the contradiction between educator and student and, made the true, clear and accountable dialog, your bigger principle in the interaction with the community.
Keywords: Comunidade e escola; Metodologia; Projeto sócio-educacional; Ação comunicativa; Significado e sentido; Educação dialógica; CIENCIAS HUMANAS::EDUCACAO